Fri 29 Apr, 2016 12:30 pm
I have no idea how to solve this logic proof, please help!
(3)I=E /(conclusion) I>G
Any help would be greatly appreciated! (Key: "&"= and, ">"= if_then_, "~"= not, "v"= or, "="= if and only if
method of BACKWARD FELL SWOOP
The only values which make the conclusion false, are I is true and G is false. Put those into the conjunction of the premises and show that that conjunction turns out to be false using those values. This would prove the argument valid since only a conjunction of false premises gives a false conclusion. Conversely if the conjunction of premises was true using those values for the conclusion to be false, the argument would be invalid.
Note that if you do that, premise 2 will be false, making the conjunction of 1 & 2 & 3 false.